New Middle Palaeolithic sites from the Mani Peninsula, Southern Greece. (2nd January 2016) - Tourloukis, Vangelis; Thompson, Nicholas; Garefalakis, Charalampos; Karkanas, Panagiotis; Konidaris, George E.; Panagopoulou, Eleni; Harvati, Katerina
Abstract : We here report the first results from a systematic research project in Mani (Southern Greece), which includes survey and test excavations. Forty-six caves, rockshelters and open-air sites in lowland settings were surveyed. Geomorphological data were collected in order to assess how geological processes affect the preservation of sites and bias site distribution patterns. Artifacts manufactured from non-local rock indicate potential raw material transfers and suggest links among the different regions of Mani, related to mobility patterns. Our research in the Mani has nearly doubled the number of known Middle Palaeolithic sites from the region and confirmed that the peninsula has the strongest 'Neanderthal signal' identified to date in Greece. Almost all sites are located at coastal areas. Despite the influence of Pleistocene landscape dynamics, this distribution emerges as a persistent pattern, perhaps indicating a preference for coastal locations. The Neanderthal occupation of Mani can illuminate important aspects of Middle Palaeolithic adaptation in one of the southernmost coastal regions of Europe.